Human Degenerate Discs Show Increased Activation of Intracellular Signalling Pathways of IL-1. (May 2014) - Daniels, J.; Binch, A. LA.; Dunn, S.; Phillips, K. L.; Chiverton, N.; Cole, A.; Michael, A. R.; Breakwell, L.; Le Maitre, C. L.
Introduction: Intervertebral disc degeneration is implicated in 40% of low back pain cases. Interleukin 1 (IL-1) is known to be important in the pathogenesis of intervertebral disc (IVD) degeneration, here we investigated the intracellular signaling pathways activated by IL-1 and determined the activation status of these pathways in native IVD tissues highlighting potential pathways for new therapies. Materials and Methods: Human nucleus pulposus cells (NP) removed during discetomy for nerve root pain were stimulated with IL-1 for 30 minutes. The activation of ERK1/2, p38, c-jun, and IκB were determined using cell-based enzyme-linked immunosorbent assays, in addition pNFκB localisation in stimulated cells was determined using immunohistochemistry. Localisation of phosphorylated c-jun, p38, ERK1/2, and NFκB together with IL-1 was investigated within paraffin embedded sections of human IVD to investigate the presence of active pathways in vivo . Pretreatment with inhibitors of p38, c-jun, and NFκB for 30 minutes before stimulation with IL-1 (10 ng/mL) for 48 hours was investigated to determine the ability of individual signaling inhibitors to block the catabolic responses induced by IL-1. Results: IL-1-induced activation of p38, MAPK, ERK ½, JNK/c-jun, and NFκB signaling pathways in human NP cells. IVD tissue samples displayed immunopositive staining for phosphorylated c-jun, ERK1/2, NFκB, and p38, immunopositivity was significantly increased within degenerate discs, particularly in those discs which also expressed high levels of IL-1. Inhibition of individual signaling pathways demonstrated differential regulation of the pleathora of IL-1-induced catabolic events, with different signaling molecules shown to regulate matrix metalloproteases, cytokines, and factors involved in innervation and angiogenesis of the disc. Conclusion: Here, we have shown that the signaling pathways activated by IL-1 in vitro display increased activation in vivo during disc degeneration. Inhibitors of these pathways demonstrated multiple signaling pathways were involved in the pleathora of IL-1 actions. Thus, inhibition of signaling pathways could be a novel mechanism to inhibit catabolic processes which could hold promise to inhibit degeneration at early stages of disease but also create the correct tissue niche to promote regeneration of the disc. Disclosure of Interest None declared